(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article examines the evolution of Balzac’s creative method, which is also expressed in the art of depicting a person. In which he painted his characters in such a way that their entire mental life was subject to one dominant passion, depicted solid figures devoid of internal contradictions, and demonstrated how one of the character traits takes possession of the entire psyche of the character. If he portrayed characters in the process of change, then he showed the changes taking place in them as a complete rejection of the features that were previously inherent in them (compare in this respect the evolution of Rastignac).